Promising Themes in Tobacco Control Campaign Message Development: A Review of Professor Xiaoquan Zhao’s Lecture at Peking University - Yan, Jiachen (The Journal of Medicine, Humanity and Media, 2025)
Tobacco use remains a pervasive global public‑health challenge, making the strategic design of persuasive messages central to modern tobacco‑control efforts. Yet a persistent gap separates theoretically robust intervention models from their practical implementation, particularly within politically and culturally constrained settings. Drawing on Professor Xiaoquan Zhao — Editor‑in‑Chief of Health Communication — and his 2025 lecture at Peking University, this review distils four decades of scholarship on tobacco‑control message design. It synthesises three leading behaviour‑change frameworks—the Theory of Planned Behaviour, Social Cognitive Theory, and the Expectancy–Value Model—and demonstrates how belief‑selection tools, notably the Promising Beliefs Selection Framework and the Relative Promise Index, operationalise these theories into actionable campaign elements. The review also appraises evidence on the alignment of content and execution strategies, maps structural constraints such as political sensitivities, media regulation, and resource limitations, and catalogues adaptive tactics reported across diverse sociocultural contexts. By retracing the field’s historical inflection points and revisiting past debates, scholars can uncover overlooked questions and gain fresh perspectives that enrich contemporary tobacco‑control communication.